Selenium Attenuates HPV-18 Associated Apoptosis in Embryo-Derived Trophoblastic Cells but Not Inner Cell Mass In Vitro - Jennifer A. Tolen; Penelope Duerksen-Hughes; Kathleen Lau; Philip J. Chan (Hindawi Limited, 2015)
Objectives. Human papillomaviruses (HPV) are associated with cell cycle arrest. This study focused on antioxidant selenomethionine (SeMet) inhibition of HPV-mediated necrosis. The objectives were to determine HPV-18 effects on embryonic cells and to evaluate SeMet in blocking HPV-18 effects. Methods. Fertilized mouse embryos were cultured for 5 days to implanted trophoblasts and exposed to either control medium (group 1), HPV-18 (group 2), combined HPV-18 and 0.5 µM SeMet (group 3), or combined HPV-18 and 5.0 µM SeMet (group 4). After 48 hrs, trophoblast integrity and, apoptosis/necrosis were assessed using morphometric and dual-stain fluorescence assays, respectively. Results. HPV-18 exposed trophoblasts nuclei (253.8 ± 28.5 sq·µ) were 29% smaller than controls (355.6 ± 35.9 sq·µ). Supplementation with 0.5 and 5.0 µM SeMet prevented nuclear shrinkage after HPV-18 exposure. HPV-18 infected trophoblasts remained larger with SeMet supplementation. HPV-18 decreased cell viability by 44% but SeMet supplementation sustained cell viability. Apoptosis was lower when SeMet was present. HPV-18 decreased inner cell mass (ICM) viability by over 60%. Conclusions. HPV-18 decreased nuclear size and trophoblast viability but these effects were attenuated by the antioxidant SeMet. SeMet blocked HPV-18 associated apoptosis process in trophoblasts but not ICM cells suggesting involvement of different oxidative stress pathways.